Social capital and debt contracting: evidence from bank loans and public bonds - Iftekhar Hasan; Chun-Keung (Stan) Hoi; Qiang Wu; Hao Zhang (Bank of Finland, 2015)
We find that firms headquartered in U.S. counties with higher levels of social capital incur lower bank loan spreads. This finding is robust to using organ donation as an alternative social-capital measure and incremental to the effects of religiosity, corporate social responsibility, and tax avoidance. We identify the causal relation using companies with a social-capital-changing headquarter relocation. We also find that high-social-capital firms face loosened nonprice loan terms, incur lower at-issue bond spreads, and prefer bonds over loans. We conclude that debt holders perceive social capital as providing environmental pressure constraining opportunistic firm behaviors in debt contracting.
URN:NBN:fi:bof-201511201442
Keywords: G21; G32; Z13; 330